Optimal allocation and sizing of distributed generation in distribution system via firefly algorithm - Mohd Herwan, Sulaiman, Dr.; Mohd Wazir, Mustafa, Prof. Dr.; Azralmukmin, Azmi; Omar, Aliman; Siti Rafidah, Abdul Rahim (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/